Relationships between women in Sarah Daniels' play "Neaptide" - Wan Yahya, Wan Roselezam (Universiti Putra Malaysia Press, 2005)
This paper is an exploration of female relationships using feminist and psychoanalytic approaches in reading a British play "Neaptide." The findings provide us a unique way of explaining the bondage between mother-daughter relationships, and it also tells us that in the play "Neaptide" Sarah Daniels offers a positive future to her two female protagonists because both have been rescued by their mother Joyce. Daniels uses the Demeter-Persephone myth to illustrate the limited choices that her female character Joyce has in handling her family crisis. Like Demeter,Joyce keeps her family together by delivering them from male domination: Val from her unhappy marriage with Colin, and Claire and Poppy from the devious and ruthless Lawrence. Claire's bold and honest public confession of herself as a lesbian has clearly entailed suffering and sacrifice. However, Joyce has made the right decision to help both her daughters to get out of their predicaments.